The effective of utilization Blending learning on academic achievement in Biology course of second class students in secondary special schools in Omdurman Locality and attitudes towards it. (Journal Of Educational and Psychological Researches, 2013)
This research aimed to definite Blending learning (BL) technique, and to know the impact of its use onacademic achievement in Biology course of second class students in secondary special schools in Omdurman Locality and attitudes towards it, to achieve this; researcher adopted the experimental method. The sample was selected of (41) students, chosen from Atabiyah school, were divided into two equals groups: one experimental group reached (26) students studied by using the  BL technique, and the second control group (25) students have been taught in the traditional method.   Data has collected by using two tools: achievement test and a questionnaire for measuring the attitudes towards Blending learning. On the light of the research questions and hypothesis; data were processed by using appropriate statistical methods. The most important results of the research as follows:There are differences of statistical significance, at the level of (0.05) between the averages of the degrees of experimental group students who have studied by BL, and the averages of the degrees of control group who studied by traditional method in the post achievement test, in favor of the experimental group.There are positive attitudes of statistical significance, at the level of (0.05) for the sample who responded to the questionnaire for measuring the attitudes towards BL.  The researcher concluded his studies with a number of recommendations and suggestions.Keywords: Blending learning,Academic achievement, Biology course, Students of the second secondary class, Attitudes towards Blending learning.